Is 'overtourism' a new issue in tourism development or just a new term for an already known phenomenon?. Issue 18 (16th September 2020) - Capocchi, Alessandro; Vallone, Cinzia; Amaduzzi, Andrea; Pierotti, Mariarita
ABSTRACT: Is overtourism a new issue in tourism development, or just a new term for an existing phenomenon? The problems caused in some destinations by the increasing growth in tourism have resulted in the recent introduction of the term 'overtourism', recalling issues discussed in the literature since the early '70s. This paper aims to answer the question of whether overtourism is a novel issue through an initial exploratory study.